Negotiating through a mediator - Golann, Dwight (Henry Stewart Talks, 2011)
Approaches to advocacy, Borrowing a mediator's powers, Selecting a mediator, Securing presence of decisionmakers, Premediation interventions, Preparing the client, Goals for the opening session, Focusing the agenda, Using the mediator's neutrality, Asking for information, Changing opponent's view of merits, Choices and tactics for the first caucus meeting, Resetting the agenda in later caucuses, Influencing final offers, Responses to impasse